REDRESSING ATROCITIES OF WAR IN BIAFRA: A MATTER OF AMNESIA OR PROSECUTIONS? - Emmanuel, Ibezim (Commonwealth Law Review Journal, 2021)
The Nigerian Civil War, otherwise known as the Biafran War raged between 1967 and 1970. Despite strident allegations of genocide, no one seems to have been investigated, indicted or prosecuted, either for genocide or crimes against humanity and war crimes. Could this be a matter of amnesia, or that of legal problematics like statutory limitations, lack of documentary evidence or the determination of what qualifies as genocide, when judged against the general notion, as an International Observer Group may have done, and arrived at the conclusion that no genocide took place in Biafra? This article examines the issues and makes a case for holding perpetrators of atrocities of war in Biafra accountable, notwithstanding the passage of 50 years, since the end of the war.